A justa causa e sua exigência para se deflagrar ação penal como expressão do direito de não ser réu - Villas, Francelle Barcelos (2022)
This dissertation, guided by the inductive method, aims to analyze Brazilian legislation, the doctrine and jurisprudence of the STF and STJ, in order to conclude and elucidate the solution adopted by the Judiciary, regarding the requirement or not of the existence of minimum evidentiary support for the receipt of the complaint in criminal proceedings. To conclude if the position is still embraced by the magistrates, of receiving the accusatory piece stripped of any reasoning, it is enough for the MP to describe in the complaint a typical fact and point out the authorship, in a petition unaccompanied by at least evidential elements, so that after, only during the procedural instruction, see if there will be evidence of criminal authorship and materiality. It is noteworthy that the admissibility of the accusation is assessed when the requirements of article 41 of the CPC are met, without the complaint incurring the inadequacies of article 395 of the CPC. In order to fulfill the proposed objective, theoretical premises necessary for understanding the problem are approached, such as criminal procedural systems, the principle of contradictory and full defense, the presumption of innocence and due process of law. Afterwards, the pre-procedural phase is entered, reflecting on the moment of the police investigation, the implicit penalties of the indictment and the possibility of the existence of the mitigated exercise of the adversary system and ample defense on the part of the investigated. Then, the procedural moment begins, with the filing of the complaint, analyzing all the criminal conditions of the action, the need for reasoning by the magistrate of the decision that receives the complaint – removing the legality of the old automated decisions made by the notaries, without any analysis of the presence of minimal evidence of authorship –, the relationship of in dubio pro reo and in dubio pro societate with the receipt of the complaint, the reflexes of the presumption of innocence for receiving the complaint and the distribution of the burden of proof considering the presumption of innocence. It is concluded that, in the light of the understanding of the Superior Courts and the doctrine, there is a right not to become a defendant in a criminal action, either by the possibility of defense in the pre-procedural phase, or by the duty of reasoning and consequent analysis of the presence of just cause for receiving the complaint, that is, the duty to observe the presumption of innocence throughout the criminal prosecution with the respective removal from the in dubio pro societate, mainly for the reception of the initial accusation.